2013
DOI: 10.1002/adfm.201300198
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylates versus Fluorines: Boosting the Emission Properties of Commercial BODIPYs in Liquid and Solid Media

Abstract: Scheme 2 . Synthetic routes of derivatives 6 , 8 , and 15 from parent dye PM597. Scheme 1 . Synthetic routes of derivatives 2 , 7 , and 11 from parent dye PM567.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 84 publications
1
54
0
1
Order By: Relevance
“…On the other hand, we had also observed that, in the case of O -BODIPYs involving carboxyl units attached to the boron, those having electron-withdrawing (EW) substituted carboxyls showed higher fluorescence quantum yields. 41 Therefore, we decided to introduce EW bromine groups in the BINOL moiety of ( R )- 1 and ( S )- 1 to generate new chiral dyes ( R )- 2 and ( S )- 2 (Figure 1). The introduced bromines are expected to have a triple effect on the dye properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we had also observed that, in the case of O -BODIPYs involving carboxyl units attached to the boron, those having electron-withdrawing (EW) substituted carboxyls showed higher fluorescence quantum yields. 41 Therefore, we decided to introduce EW bromine groups in the BINOL moiety of ( R )- 1 and ( S )- 1 to generate new chiral dyes ( R )- 2 and ( S )- 2 (Figure 1). The introduced bromines are expected to have a triple effect on the dye properties.…”
Section: Resultsmentioning
confidence: 99%
“…This result confirms, once again, the positive influence of EW groups attached to the O -moiety over the fluorescence of the O -BODIPY. 41 …”
Section: Resultsmentioning
confidence: 99%
“…Replacement of the Fa toms by alkoxy,p henoxy, [31] alkynyl, [32] aryl, [33] heteroaryl, [34] Cl, [35] and carboxylatem oieties, [36] has been reported. However,t hese transformations, thoughi nteresting, lie beyondt he scope of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…The bathochromic shifts in the absorption and emission spectra, and the increase in the photoluminescence quantum yield of PM567 in limonene with respect to ethyl acetate, are very similar to those shown by PM567 in cyclohexane. 34 This is not surprising, since both solvents, cyclohexane and limonene, are very similar low-polar hydrocarbons.…”
Section: Resultsmentioning
confidence: 95%